HUBUNGAN GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIFITAS (GPPH) TERHADAP STATUS GIZI ANAK DI KLINIK TUMBUH KEMBANG RSUP SANGLAH DENPASAR - Gusti Ayu Teja Devi Megapuspita; I Gusti Ayu Trisna Windiani; I Gusti Agung Ngurah Sugitha Adnyana (Universitas Udayana, 2017)
Attention Deficit/Hyperactivity Disorder (ADHD) consists of a pattern that shows signs of persistent inattention and / or impulsive behavior and hyperactivity, which are heavier than they should occur at the age of developmentDAss. Children with ADHD have more physical activity than children without GPPH that affect their nutritional status. The aim of this study was to determine the relationship Attention Deficit/Hyperactivity Disorder (ADHD) and nutritional status of children in Growth and Development Clinic Sanglah Hospital. This research method analytical cross-sectional, that taken from the register of children with ADHD in Growth and Development Clinic Sanglah Hospital on January 1, 2014 - August 31, 2016. The results of 120 samples consisting of 48 ADHD children and 72 of non-ADHD children. The relationships of ADHD with normal and abnormal nutritional status is significant (PR: 0.5, 95% CI : 0.26; 0.97, p = 0.028), thin and normal nutritional status are also significant (PR: 0.2, 95% CI : 0.48; 0.835, p = 0.001), whereas the obese and normal nutritional status was not significant (PR: 0.875, 95% CI : 0.37; 2.06, p = 0.759). The conclusions of this study there is a significant relationship between ADHD and nutritional status (p = 0.028), where the prevalence of abnormal nutritional status in the children with ADHD is half lower than the children in non-ADHD group. Keywords: attention deficit and hyperactivity disorders, nutritional status, malnutrition, overweight.